Personal-Social Guidance And Counseling Program In Shaping Youth Self-Concepts At Ar-Rahmah Orphanage - Harry Harry; Didin Hafidhuddin (Prophetic guidance and counseling journal, 2020)
The condition of children in orphanages who experience psychological pressure because they have to enter the new environment and new habits and away from their families causes them to have a negative self-concept. Negative self-concepts will form despicable attitudes and behaviors that will inhibit their physical and mental growth and development. Therefore, efforts are needed to restore their psychological with personal-social guidance and counseling so that children have a positive self-concept.  The purpose of this study is to analyze the social-personal guidance and counseling program at Ar-Rahmah Orphanage in making teenage self-concepts. The method used in this research is descriptive qualitative. Data collection techniques carried out by observation, interviews, and documentation. The results shows that: personal-social guidance and counseling program at the Ar-Rahmah Orphanage had not yet been found in a structured and systematic written form. The form of activities of the personal-social guidance and counseling program at the orphanage consists of basic services and responsive services. Basic services include recitation, division of duty picks, muhadarah, learning English, habituation in worship and learning to knit. The form of responsive services is a face-to-face meeting between caregivers and orphanage children once a week and provides guidance for children who have problems.